Toxoplasma gondii infection in people with schizophrenia is related to higher hair glucocorticoid levels - Beaumont, Emy; Brodeur, Jacques; Thomas, Frédéric; Dujon, Antoine M.; ,; Consortium Signature; Lupien, Sonia J. (Frontiers in Psychiatry, 2024)
Toxoplasma gondii (TG) is a common protozoan parasite infecting approximately one third of the human population. Animal studies have shown that this parasite can manipulate its host behavior. Based on this, human studies have assessed if TG can be involved in mental health disorders associated with important behavioral modifications such as schizophrenia. However, results have been discrepant. Given that TG has a strong impact on fear and risk-taking processes in animal studies and that fear and risk-taking behaviors are associated with the human stress response, we tested whether glucocorticoid biomarkers (salivary and hair) differ in people with schizophrenia and controls as a function of TG status. We measured TG antibodies in blood samples, as well as salivary and hair glucocorticoid levels in 226 people with schizophrenia (19.9 % women, mean age = 39 years old) and 129 healthy individuals (controls) (45.7% women, mean age = 41 years old). The results showed that people with schizophrenia infected with TG presented significantly higher hair glucocorticoid concentrations than non-infected schizophrenic patients. This effect was not found in control participants. No effect was observed for salivary glucocorticoid levels. Additionally, there were no associations between TG infection and positive psychotic symptoms nor impulsivity. These results show that people with schizophrenia present high levels of hair glucocorticoid levels only when they are infected with TG. Further studies performed in populations suffering from other mental health disorders are needed to determine if this effect is specific to schizophrenia, or whether it is generalized across mental health disorders.